Modern global and domestic trends in the development of the telecommunications industry - Makalakova, B.M. (KU Publ., 2020)
The article is devoted to an overview of modern world and domestic trends in the development of the world communications market, telecommunications services and paid TV services in the telecommunications industry. Much attention is paid to the analysis of the main trends in the telecommunications market in 2019 in Kazakhstan, in particular - the fixed telephony market, the mobile communications mаrket, the broadband Internet access market, the IP telephony market.
Keywords: telecommunications; telecommunications industry; telecommunications services market